PASS: Peer-aware Silence Suppression for Internet Voice Conferences - Xu, Xun; He, Li-wei; Florencio, Dinei; Rui, Yong (ICME, 2006)
A novel tandem-free solution for multiparty VoIP conferences called PASS (Peer-Aware Silence Suppression) is presented. Similar to traditional tandem-free solutions, PASS introduces a limit on the number of concurrent speakers in a conference. But in contrast to traditional solutions, PASS silence suppression and speaker selection are completely distributed, running on each client. No speaker selection is performed at the bridge at all. This configuration leads to better scalability, lower bandwidth occupation and jitter buffer delay, and higher compatibility with a wide variety of network topologies. The key component of PASS, distributed silence suppression and speaker selection, is realized through a robust approach proposed in this paper. Based on a voice activity measure derived using machine learning techniques, this approach is able to reliably suppress silence in complex environments, and perform accurate and transparent speaker selection as well.